KERAGAAN KESESUAIAN LAHAN DAN STRATEGI PENGELOLAAN PERKEBUNAN KELAPA SAWIT PLASMA BERKELANJUTAN - Putu Wigena, I Gusti; Subardjal, Djadja; , Andriati; Sudana, Wayan (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2008)
Land Suitability Performance and Sustainable Management Strategic of Public Oil Palm Plantation. The great quantities of stakeholders involved and their different conflict of interests in the oil palm management is unfavorable, as characterized by the decrease of land productivity and the high-polluted environment. This condition led to create a holistic solution in order to achieve sustainable oil palm management. For this reason, researches on land suitability and public oil palm plantation strategy have been done from January to December 2007. The experimental site was public oil palm plantation of PTP Nusantara V Sei Pagar, Perhentian Raja Sub District Kampar Districts, Riau Province. Land suitability method was developed by Djaenudin et all. (2003) in which the public oil palm plantation strategy is analyzed by using Prospective Analysis. The research showed that land suitability in the majority of land experiment (75%) can be grouped into S2-f that is moderately suitable with nutrients retention as main limiting factor due to the lower pH of the soil. The land suitability in the remaining areas (about 25%) can be classified into S2-f,n that is moderately suitable with nutrients retention and nutrients supply as limiting factors due to the lower of pH and caption exchange capacity (CEC) values. Productivity level of the land by average was 23.04 tons fruit bunches/ha/year or equal to 91% of potential yield. There were 7 key factors that should be considered in order to achieve the sustainable management of public oil palm plantation, namely land occupation status, land suitability, land size, human resources, working capital, institution and government policies. Based on the probability of occurrence, a medium setting management becomes as a promotion strategy to achieve sustainable condition of public oil palm management. The condition of this situation was land occupation status should be guaranteed (certificated), land suitability and land size remain the same as the current condition, the availability of working capital provided by government, qualified human resources in managing oil palm (educational level and skill improved), linkage institution was actively seeking solution and government policies should be supportive in implementing the selected state. Key words: Public oilp palm plantation, sustainability, suitability, strategic managemen Banyaknya pihak yang terlibat dan terjadinya benturan kepentingan menyebabkan pengelolaan perkebunan kelapa sawit plasma kurang tepat yang dicirikan oleh semakin menurunnya produktivitas lahan dan pencemaran terhadap lingkungan. Untuk itu, telah dilakukan penelitian tingkat kesesuaian lahan dan strategi pengelolaan perkebunan kelapa sawit plasma berkelanjutan dari bulan Januari sampai Desember 2007. Lokasi penelitian di perkebunan kelapa sawit plasma PT. Perkebunan Nusantara V Sei Pagar, Kecamatan Perhentian Raja Kabupaten Kampar Provinsi Riau. Tingkat kesesuaian lahan menggunakan metode yang dikembangkan oleh Djaenudin et al., strategi pengelolaan perkebunan kelapa sawit plasma dianalisis dengan menggunakan Analisis Prospektif. Hasil penelitian menunjukkan bahwa tingkat kesesuaian lahan di lokasi penelitian sebagian besar (75%) termasuk S2-f yaitu cukup sesuai dengan faktor pembatas retensi unsur hara berkaitan dengan pH tanah. Sekitar 25% tingkat kesesuaiannya termasuk S2-f,n yaitu kelas cukup sesuai dengan faktor pembatasketersediaan hara rendah dan retensi hara tinggi berkaitan dengan KTK tanah masam dan pH tanah rendah. Rata-rata produktivitas kelapa sawit pada lahan ini 23,04 t TBS/ha/tahun atau setinggi 91% dari produktivitas potensialnya. Terdapat tujuh faktor kunci yang hams dipertimbangkan untuk mencapai kondisi perkebunan kelapa sawit berkelanjutan yaitu status penguasaan lahan, kesesuaian lahan, luas lahan, sumberdaya manusia, modal, kelembagaan dan kebijakan pemerintah. Berdasarkan urutan peluang kejadiannya, skenario pengelolaan medium merupakan strategi yang paling memungkinkan untuk mencapai kondisi pengelolaan perkebunan kelapa sawit plasma berkelanjutan. Salah satu kondisi yang mewakili skenario ini adalah luas lahan tetap, status penguasaan lahan terjamin (bersertifikat), kesesuaian lahan tetapi (karena teknologi), modal kerja cukup tersedia, kualitas SDM cukup memadai (pendidikan dan keterampilan petani membaik), instansi terkait cukup aktif (kelembagaan agak kuat) dan kebijakan pemerintah agak mendukung. Kata kunci Kelapa sawit plasma, berkelanjutan, kesesuaian lahan, analisis prospektif, skenario strategis